Quantitative evaluation of waste sorting management policies in China’s major cities based on the PMC index model - Xu, Jiangtao; Zhang, Zaisheng; Xu, Yanqing; Liu, Li; Pei, Tong (Frontiers in Environmental Science, 2023)
Municipal Solid Waste governance in China entered a new phase in March 2017 when the Chinese government began requiring major cities to enforce waste sorting as well as to develop a system of laws, regulations, and standards regarding waste sorting. This study used text mining and the Policy Modeling Consistency (PMC) Index model to develop an evaluation system of Municipal Solid Waste sorting management policies that included 10 first-level variables and 51 second-level variables to quantitatively evaluate the texts of waste sorting management policies in 11 major cities, and then the PMC surface of policy texts was constructed to analyze the strengths and weaknesses of individual policies according to the PMC index values. The results revealed that there were no excellent level or bad level policies among the 11 policies, with an average PMC index value of 7.71. Overall, the 11 policy texts all set out clear goals and programs in accordance with local conditions, but there are some differences across policies in terms of indicators, including policy content, policy function, policy evaluation, restriction and incentives. This study provides a fresh viewpoint on the policy evaluation of waste sorting management and offers some insight for policymakers, who should pay attention to waste separation, focus on key indicators of the policy, and enhance the effectiveness of the policy response. In addition, the applicability of the evaluation model and the difficulties associated with waste sorting governance of China in post-epidemic are discussed.